Themes, Procedures and Strategies that lead to Conflict Transformation and Management Primary School Curriculum in Zimbabwe. - Saiden, Thondhlana (Advances in Social Sciences Research Journal, 2017)
The study aimed at establishing themes, strategies and procedures that could lead to the crafting of a primary school conflict transformation and management curriculum. It was a qualitative study. It adopted a case study design. The instruments employed were a review of related literature tool, open ended questionnaires and focus group protocol. The sample consisted of 227 teachers and 120 children purposively chosen. The major findings were that strategies such as negotiation, arbitration and mediation, procedures such as academic controversy, creating a cooperative environment, circle time, pastoral care and peer support and training and different themes for content, methodology, assessment and management and administration in schools and classrooms should guide the crafting the conflict transformation and management of the primary schools. The study recommended that the Curriculum Development Unit of the Ministry of Primary and Secondary Education in Zimbabwe be guided by the following strategies, procedures and themes in crafting the conflict transformation and management primary school curriculum and that other African countries could find the strategies, procedures and themes useful in crafting a similar curriculum.